Investigation the Effects of the Gasoline Price Increment Policy and Subsidy on Consumer Prices Indices and Welfare of Households’ Groups - Nooraddin Sharify (پژوهشهای اقتصادی, 2021)
To prevent gasoline smuggling to abroad and its excessive consumption in the country, the price of gasoline increased and gasoline was quoted in 2019. This policy has affected the consumption expenditures of different income groups of households. To compensate the expenditures increment, the government pays subsidies to some income groups of households. This paper investigates the effects of this policy on the consumption expenditures of different income deciles in urban and rural areas and compares them with gasoline subsidies. To this end, a developed version of implicit subsidy elimination model is employed. The input-output table of Iran for the year 2016 is used as database of the research. The results of the research indicate that the subsidy of the government will cover the consumption expenditure increment due to its gasoline price policy for all target income groups. However, this policy fails to compensate the increment of the consumption expenditure in the case in which the labour force and capital owners adjust their endowments and the exchange rate is changed with respect to domestic price inflation.